2012
DOI: 10.1007/978-1-62703-023-6_7
|View full text |Cite
|
Sign up to set email alerts
|

Studying Substrate Binding to Reconstituted Secondary Transporters by Attenuated Total Reflection Infrared Difference Spectroscopy

Abstract: The determination of protein conformational changes induced by the interaction of substrates with secondary transporters is an important step toward the elucidation of their transport mechanism. Since conformational changes in a protein alter its vibrational patterns, they can be detected with high sensitivity by infrared difference (IR(diff)) spectroscopy without the need for external probes. We describe a general procedure to obtain substrate-induced IR(diff) spectra by alternating perfusion of buffers over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…The exact dependence between film swelling and the ionic strength of the buffer will depend, among other factors, on the nature of the lipids. For instance, a similar film swelling as obtained here for bR in purple membrane using 4 M NaCl was obtained for a membrane protein reconstituted in polar E. coli lipids using just 0.1 M NaCl 62 . If the sample occupies less than 5% of the probed volume consider re-doing the hydration step using a buffer of higher ionic strength.…”
mentioning
confidence: 53%
“…The exact dependence between film swelling and the ionic strength of the buffer will depend, among other factors, on the nature of the lipids. For instance, a similar film swelling as obtained here for bR in purple membrane using 4 M NaCl was obtained for a membrane protein reconstituted in polar E. coli lipids using just 0.1 M NaCl 62 . If the sample occupies less than 5% of the probed volume consider re-doing the hydration step using a buffer of higher ionic strength.…”
mentioning
confidence: 53%
“…Perfusion-induced difference attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy was first applied to study the structural changes of an acetylcholine receptor upon ligand binding (Baenziger et al 1992). The method has been well reviewed by several groups (Lorenz-Fonfria et al 2012;Nyquist et al 2001;Rich and Iwaki 2007). Here it can be confirmed that the method is also applicable to a K + ion channel and is a potential tool for studying ion selectivity among alkali metal cations.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the buffer was changed; the sample was washed, and the spectra were measured again. After the absorption spectra, measurements before and after buffer exchanges were completed four times; the difference spectra were calculated by subtraction, correction of membrane swelling changes, and nonspecific distortions associated with ion exchange according to Lórenz-Fonfría et al (44). The absolute absorption spectra of TWIK1 samples immersed in buffer solution (Fig.…”
Section: Atr-ftir Measurementsmentioning
confidence: 99%
“…The absolute absorption spectra of TWIK1 samples immersed in buffer solution (Fig. 1F) were obtained by subtracting the buffer contribution according to Lórenz-Fonfría et al (44). tion energy (52,53) and the RESP scheme (54) to describe the partial charges of the QM subsystem.…”
Section: Atr-ftir Measurementsmentioning
confidence: 99%